Research applications of dialux software in lighting module practice teaching - Đặng , Quang Khoa (Journal of Technical Education Science, 2013)
Research into software applications in vocational training process is progressive trend of modern teaching, from the above aware, during practice teaching of lighting module, we have studied the application of DIALux software to support lighting design calculations and simulation of research results, constructed, explored and learnt about the indoor and outdoor lighting model. In the framework and scope of the article only present an overview of the advantages of DIALux software, guide basic steps to design a traffic light project